Necessity of pharyngeal anesthesia during transoral gastrointestinal endoscopy: a randomized clinical trial - Tomoyuki Hayashi; Yoshiro Asahina; Yasuhito Takeda; Masaki Miyazawa; Hajime Takatori; Hidenori Kido; Jun Seishima; Noriho Iida; Kazuya Kitamura; Takeshi Terashima; Sakae Miyagi; Tadashi Toyama; et al. (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims The necessity for pharyngeal anesthesia during upper gastrointestinal endoscopy is controversial. This study aimed to compare the observation ability with and without pharyngeal anesthesia under midazolam sedation. Methods This prospective, single-blinded, randomized study included 500 patients who underwent transoral upper gastrointestinal endoscopy under intravenous midazolam sedation. Patients were randomly allocated to pharyngeal anesthesia: PA+ or PA- groups (250 patients/group). The endoscopists obtained 10 images of the oropharynx and hypopharynx. The primary outcome was the non-inferiority of the PA- group in terms of the pharyngeal observation success rate. Results The pharyngeal observation success rates in the pharyngeal anesthesia with and without (PA+ and PA-) groups were 84.0% and 72.0%, respectively. The PA- group was inferior (p=0.707, non-inferiority) to the PA+ group in terms of observable parts (8.33 vs. 8.86, p=0.006), time (67.2 vs. 58.2 seconds, p=0.001), and pain (1.21±2.37 vs. 0.68±1.78, p=0.004, 0-10 point visual analog scale). Suitable quality images of the posterior wall of the oropharynx, vocal fold, and pyriform sinus were inferior in the PA- group. Subgroup analysis showed a higher sedation level (Ramsay score ≥5) with almost no differences in the pharyngeal observation success rate between the groups. Conclusions Non-pharyngeal anesthesia showed no non-inferiority in pharyngeal observation ability. Pharyngeal anesthesia may improve pharyngeal observation ability in the hypopharynx and reduce pain. However, deeper anesthesia may reduce this difference.